Physico-chemical Study on Amorphous Structure of B2O3-PbO2 Binary System - ASHRAFI*, F.; BABANEJAD, S.A.; REZAEI, H. (Asian Journal of Chemistry, 2024)
Using optical absorption and studying the edge-absorption of either crystalline or amorphous structures, is an useful method for recognizing electronic structure of these materials. In this study, we have prepared the bulk specimens of different percentages from the melt of B2O3- PbO2 binary system and then cooled them rapidly. It was characterized by UV-visible spectrum. In comparison with Mott and Davis's statement, it was established that the type of transition is not allowed. By extra-polating the linear part of (αhω)3/2 against ( hω) diagram, the energy of optical gap (Eopt) at (αhω)3/2 = 0 was determined. Obtained amounts of optical gap energy (Eopt = 0.2500 to 3.0735 eV) showed an increased with increasing of PbO2 mass percentage. Amounts of constant of proportion B is determined by using Mott and Davis relation.